Grain-oriented electrical steel sheet

KR103032478B1Active Publication Date: 2026-10-13JFE STEEL CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020247025840
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-02-17
Filing Date
2023-02-17
Publication Date
2026-10-13
Estimated Expiration
2043-02-17

Smart Images

  • Figure 112024083206470-PCT00007_ABST
    Figure 112024083206470-PCT00007_ABST
Patent Text Reader

Abstract

The present invention provides a oriented electrical steel sheet having good film adhesion. Among the elements present at the grain boundaries between ceramic particles included in the underlayer film of the oriented electrical steel sheet, one or both of S and Se elements are present in a range of 0.02 to 2.00 at%.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a oriented electrical steel sheet suitable for use as a core material for transformers. Background Technology

[0002] Grained electrical steel is a soft magnetic material used as a core material for transformers or large generators, and has a crystal texture in which the <001> axis of the crystal orientation, which is the easy magnetization axis of iron, is highly ordered in the rolling direction of the steel sheet. Such a crystal texture is achieved by preferentially growing the {110}<001> orientation grains, called the Goss orientation, through secondary recrystallization.

[0003] In oriented electrical steel sheets, iron loss characteristics are of the utmost importance. Iron loss characteristics represent the energy loss when the steel sheet is excited, and a lower value indicates less loss, which is considered indicative of a superior material. Methods to reduce iron loss include minimizing the deviation of the aforementioned Goss orientation to bring it closer to the ideal Goss orientation, or performing a special processing method known as magnetic domain refining. Additionally, given that oriented electrical steel sheets are used in a laminated form, an insulating film is applied to the surface of the steel sheet, and a method is also utilized to reduce iron loss by applying tension to the steel sheet through this insulating film.

[0004] Insulating films generally have a two-layer structure consisting of a base film based on forsterite and a coating-type coating. In particular, for forsterite films, adhesion to the steel sheet is considered important in addition to the above-mentioned tensioning effect. For example, Patent Document 1 describes a technique for evaluating film adhesion based on the brightness of the irradiated area by irradiating light onto a oriented electrical steel sheet.

[0005] In order to improve the film characteristics represented by such film adhesion, a technique for fixing TiN in a forsterite film is disclosed in Patent Document 2, a technique for specifying the amounts of Ti, B, and Al in a forsterite film is disclosed in Patent Document 3, and a technique for specifying the ratio of Ti or B and N in a forsterite film is disclosed in Patent Document 4. Prior art literature

[0006] Japanese Published Patent Application No. 2011-158328, Japanese Published Patent Application No. Hei 08-291390, Japanese Published Patent Application No. Hei 10-121213, Japanese Published Patent Application No. 2012-31518 The problem to be solved

[0007] Here, although Ti or B is used in the aforementioned methods for improving film properties, these methods still left problems regarding the adhesion of the underlayer film of oriented electrical steel sheets, such as forsterite films.

[0008] The present invention has been made in consideration of the above-mentioned problems, and its objective is to obtain a oriented electrical steel sheet having excellent adhesion of an underlayer film in a oriented electrical steel sheet having an underlayer film. means of solving the problem

[0009] To solve the above problem, the inventors discovered that by introducing S or Se at the grain boundaries of the forsterite film, a directional electrical steel sheet having good film characteristics can be stably obtained, and thus completed the present invention.

[0010] Below, the experiment that led to the completion of the present invention will be described.

[0011] Experiment 1

[0012] A steel slab containing C: 0.075%, Si: 3.45%, Mn: 0.12%, and Se: 0.020% by mass, with the remainder being Fe and unavoidable impurities, was manufactured by continuous casting. After heating the slab to crack at 1400°C for 25 minutes, it was finished to a thickness of 2.4 mm by hot rolling. Subsequently, the hot-rolled plate was annealed at 950°C for 30 seconds in a dry nitrogen atmosphere. After this hot-rolled plate annealing, the surface scale was removed by acid cleaning, and the plate was further finished to a thickness of 1.5 mm by cold rolling. Subsequently, intermediate annealing was performed at 1140°C for 20 seconds, and the plate was finished to a thickness of 0.23 mm by cold rolling. Subsequently, a first recrystallization annealing accompanied by decarburization was performed at 830°C for 100 seconds under a humid atmosphere of 60 vol% H2–40 vol% N2 and a dew point of 60°C. Additionally, a second recrystallization annealing was performed by applying an annealing separator mainly composed of MgO and holding at 1200°C for 10 hours. At that time, the introduced atmosphere was varied as described in Table 1. Under all conditions, the atmosphere was N2 up to 800°C during the heating process, and an Ar atmosphere was used during the cooling process after the holding was completed.

[0013] After the second recrystallization annealing was completed, the film adhesion of the obtained sample was evaluated. Film adhesion was evaluated by winding the steel plate onto cylinders of various diameters and determining the minimum diameter of the cylinder where the film does not peel off. Additionally, a smaller minimum diameter indicates superior film adhesion.

[0014]

[0015] The evaluation results of the above film adhesion are shown in Fig. 1. As is evident from Fig. 1, conditions IV, VI, and VII exhibited excellent film adhesion. To investigate the cause, cross-sections of the forsterite films of samples from condition VI, which showed good film adhesion, and condition I, which showed slightly inferior adhesion, were cut to a thickness of approximately 50 nm using FIB processing (Helios 600i). Then, microstructure observation and elemental distribution were confirmed using an electrolytic emission transmission electron microscope (Talos F200X) equipped with an energy dispersive spectrum analyzer (EDS), under conditions of an acceleration voltage of 200 kV and a beam diameter of 1 nm or less. As a result, it was revealed that the elements localized at the forsterite grain boundaries differed depending on the condition.

[0016] Figure 2 schematically shows a cross-section of the film provided for the above experiment and also shows the location where the distribution of elements was measured. As shown in Figure 2, line analysis was performed across the forsterite grain boundaries to investigate the distribution of elements. The measurement distance was set to approximately 200 nm with respect to the grain boundaries.

[0017] Figure 3 is a schematic diagram showing the entire measurement result. Under both conditions, it can be confirmed that Mg, Si, and O exist in the stoichiometric compositional ratio of forsterite Mg2SiO4.

[0018] Here, what needs to be noted is the trace elements on the grain boundaries. In Fig. 4, only the profile of Se is superimposed and illustrated for comparison of conditions. Also, the scale of the vertical axis in Fig. 4 has been changed from Fig. 3. As is evident from the results shown in Fig. 4, the presence of a Se peak was confirmed under condition VI, which has good film adhesion, whereas no Se peak was confirmed under condition I. Furthermore, the amount of Se present (peak value) under condition VI was approximately 0.15 at%. Although not shown in the figure, a peak of Mn was also confirmed as another element. In addition, the at% in the present invention can be obtained by integrating the peak profile at the position of Se using an EDS analysis device attached to the TalosF200X, for example, when the target element is Se.

[0019] Experiment 2

[0020] A steel slab containing, in mass%, C: 0.033%, Si: 3.01%, Mn: 0.25%, Al: 0.030%, and N: 0.078%, with the remainder being Fe and unavoidable impurities, was manufactured by continuous casting. After heating the slab to crack at 1420°C for 25 minutes, it was finished to a thickness of 2.7 mm by hot rolling. Subsequently, the hot-rolled plate was annealed at 1050°C for 30 seconds in a dry nitrogen atmosphere. After the hot-rolled plate annealing, the surface scale was removed by acid cleaning, and then the plate was finished to a thickness of 1.8 mm by cold rolling. Subsequently, intermediate annealing was performed at 1080°C for 100 seconds, and the plate was finished to a thickness of 0.23 mm by cold rolling. Additionally, a first recrystallization annealing involving decarburization was performed at 840°C for 100 seconds under a humid atmosphere of 50 vol% H2–50 vol% N2 and a dew point of 45°C. Additionally, MgO was applied as an annealing separator. At that time, the conditions were divided into Condition A, in which 3 parts by mass of magnesium sulfate were added to MgO, and Condition B, in which only MgO was added. Subsequently, a second recrystallization annealing was performed at 1200°C with a holding period of 20 hours. At that time, the atmosphere applied was an H2 atmosphere for 10 hours during the first half of holding, and an Ar atmosphere for the remaining period. After the completion of the second recrystallization annealing, the film adhesion of the obtained sample was evaluated in the same manner as in Experiment 1.

[0021] The results are shown in Figure 5, but condition A exhibits excellent adhesion. When the forsterite films of these samples were examined in the same manner as in Experiment 1, a peak of S was detected at the grain boundaries in condition A, and its presence was approximately 0.05 at%. On the other hand, no peak of S was detected in condition B.

[0022] Summarizing the results of the two experiments mentioned above, concentrations of S or Se were confirmed at the forsterite grain boundaries under conditions of good film adhesion. Although the reason why film adhesion improves when S or Se is concentrated is not entirely clear, the inventors believe as follows. That is, the adhesion between the base film and the steel substrate is largely due to the anchoring effect of the base film, and the attractive interaction between the base film and the steel substrate is small. Therefore, when the base film peels off, the base film itself, containing the anchor, must be destroyed. Furthermore, in this experiment, since the destroyed base film is an aggregate of forsterite particles, fracture generally occurs at the grain boundaries.

[0023] In this experiment, S or Se is concentrated at the grain boundaries, suggesting the presence of selenides or sulfides of these S or Se. Since these are known to be softer than ceramics, they are expected to relieve stresses such as those caused by bending. Therefore, it is presumed that this stress-relieving effect suppressed fracture at the grain boundaries, thereby improving film adhesion.

[0024] In addition, the process of S or Se enriching at grain boundaries is considered as follows. For example, in Experiment 1, it is thought that Se is present in the steel and forms MnSe precipitates, i.e., inhibitors. During secondary recrystallization annealing, the inhibitors decompose by introducing mainly H2 and react with the H2 in the atmosphere to be released in the gas phase as H2Se. It is thought that this reaction becomes active in the high-temperature range, and at that point, crystal grains of forsterite are formed on the surface of the steel sheet.

[0025] In other words, when Se is vaporized from the base iron to the outside, the gas containing this Se passes through the grain boundaries of forsterite. It is believed that at this time, some of the Se segregates at the grain boundaries or forms sulfides with Mn, etc. According to this theory, if purification by H2 is promoted, the Se at the forsterite grain boundaries is also purified and disappears, so it is thought that the effect of improving film adhesion is lost.

[0026] In addition, in Experiment 2 above, although S or Se is not contained in the steel, it is thought that the presence of S at the grain boundaries of the ceramic particles included in the undercoat is due to the intrusion of S from the sulfate added to MgO. Sulfate or selenate decomposes at a relatively low temperature during secondary recrystallization annealing, causing S or Se to intrude into the steel. As a result, the same situation occurs as when S or Se was added to the material. Therefore, it is presumed that the same results as in Experiment 1 were obtained.

[0027] The present invention is completed by further examining the novel recognition above, and the gist of the invention is as follows.

[0028] 1. A oriented electrical steel sheet having a substrate film, wherein the substrate film comprises ceramic particles, and further, at the grain boundaries of the ceramic particles, one or both of S and Se are present in an amount of 0.02 to 2.00 at%.

[0029] 2. The oriented electrical steel sheet described in 1, wherein the S and Se elements are one or more sulfides or selenides selected from Mn, Ca, Sr, Cu, and Mg.

[0030] 3. A oriented electrical steel sheet as described in 1 or 2, wherein the thickness between grain boundaries of ceramic particles containing the S and Se elements is 50 nm or less.

[0031] 4. The above ceramic particles are a oriented electrical steel sheet described in any one of claims 1 to 3, which is composed of forsterite. Effects of the invention

[0032] According to the present invention, a oriented electrical steel sheet having good film properties, particularly excellent peel resistance, can be efficiently obtained. Brief explanation of the drawing

[0033] Figure 1 is a graph showing the relationship between atmosphere conditions and the minimum diameter of the cylinder where the film does not peel off. Figure 2 is a diagram schematically showing a cross-section of a film and the locations where the distribution of elements was measured. Figure 3 is a diagram showing the entire result measured at the measurement location of Figure 2. Figure 4 is a diagram showing the measurement results of Se by changing the scale of the vertical axis of Figure 3. Figure 5 is a graph showing the relationship between the conditions under which the annealing separator was changed and the minimum diameter of the cylinder where the film is not peeled off. Specific details for implementing the invention

[0034] (Form for carrying out the invention)

[0035] Hereinafter, the reasons for limiting the constituent requirements of the present invention are described. The steel sheet of the present invention is a oriented electrical steel sheet having an underlayer coating and ceramic particles included in such underlayer coating, and it is necessary that either one or both of S and Se elements are present at the grain boundaries of the ceramic particles in the range of 0.02 to 2.00 at%. If it falls outside this range, the bending peeling characteristics deteriorate. Preferably, the lower limit is 0.04 at% and the upper limit is 0.50 at%.

[0036] In addition, in the present invention, as shown in FIG. 4 above, the grain boundaries of the ceramic particles are scanned, and the peak values ​​of S and / or Se are set to the at% of S and / or Se. In addition, in the present invention, 50 ceramic grain boundaries are measured, and the average value of the total number is set to the at%. Furthermore, in the present invention, not only the average value but also 50% of the measurement locations fall within the at%, thereby more advantageously obtaining the effects of the present invention.

[0037] In addition, it is preferable that these S and / or Se exist as one or more sulfides and / or selenides selected from Mn, Ca, Sr, Cu, and Mg, respectively. This is because, as mentioned above, these materials are softer compared to ceramic particles and are thought to be able to relieve stress such as bending.

[0038] Here, among the grain boundaries of these ceramic particles, it is preferable that the thickness between the grain boundaries of the ceramic particles in which S and / or Se elements are present be 50 nm or less. This is because if it exceeds 50 nm, the layer of S and / or Se elements itself is destroyed by bending processing.

[0039] In addition, the definition of such thickness is twice the half-width of the S and / or Se element peaks obtained by line analysis using the above Talos. Furthermore, in the present invention, the thickness is defined as the measured value (the average value of the total number) within the following range.

[0040] Next, the composition of a suitable steel material (slab) used for manufacturing the oriented electrical steel sheet of the present invention will be described.

[0041] C: 0.020∼0.100mass%

[0042] If the C content does not meet 0.020 mass%, the precipitation of fine carbides is insufficient or the steel structure of the material becomes an α-single phase, which causes the steel to become embrittled during casting or hot rolling, leading to cracks in the slab or edge cracks on the steel sheet edges after hot rolling, and making it prone to causing defects that hinder manufacturing. On the other hand, if it exceeds 0.100 mass%, it becomes difficult to reduce it to 0.005 mass% or less, where self-aging does not occur, through decarburization annealing. Therefore, the C content is preferably in the range of 0.020 to 0.100 mass%. More preferably, the lower limit is 0.025 mass% and the upper limit is 0.080 mass%.

[0043] Si: 2.00∼5.00 mass%

[0044] Si is an element necessary to increase the resistivity of steel and reduce iron loss. There is a concern that the above effect may not be sufficient if the amount is less than 2.00 mass%. On the other hand, if it exceeds 5.00 mass%, workability decreases, making it difficult to manufacture by rolling. Therefore, the Si content is preferably in the range of 2.00 to 5.00 mass%. More preferably, the lower limit is 2.50 mass% and the upper limit is 4.00 mass%.

[0045] Mn: 0.01∼1.00 mass%

[0046] Mn is an element necessary to improve the hot workability of steel. There is a concern that the above effect may not be sufficient if it is less than 0.01 mass%. On the other hand, if it exceeds 1.00 mass%, the magnetic flux density of the product plate decreases. Therefore, the Mn content is preferably in the range of 0.01 to 1.00 mass%. More preferably, the lower limit is 0.02 mass% and the upper limit is 0.30 mass%.

[0047] For components other than these, there are cases where an inhibitor is used to induce secondary recrystallization and cases where it is not.

[0048] First, when using an inhibitor to induce secondary recrystallization, for example, when using an AlN-based inhibitor, it is preferable to include Al and N in the ranges of Al: 0.0100–0.0400 mass% and N: 0.0030–0.0150 mass%, respectively. In addition, when using a MnS·MnSe-based inhibitor, it is preferable to include the aforementioned amount of Mn and one or two of S: 0.002–0.030 mass% and Se: 0.003–0.030 mass%. If the amount added is less than the lower limit value, there is a risk that the inhibitor effect may not be sufficiently obtained. On the other hand, if it exceeds the upper limit value, the inhibitor component remains undissolved during slab heating, causing a deterioration in magnetic properties. Furthermore, AlN-based and MnS·MnSe-based inhibitors may be used in combination.

[0049] Meanwhile, in cases where an inhibitor is not used to induce secondary recrystallization, it is preferable to use a steel material in which the content of Al, N, S, and Se, which are the aforementioned inhibitor-forming components, is reduced as much as possible, with Al: less than 0.010 mass%, N: less than 0.0050 mass%, S: less than 0.005 mass%, and Se: less than 0.005 mass%.

[0050] In addition, the remainder other than the above components is Fe and unavoidable impurities.

[0051] The oriented electrical steel sheet of the present invention, in addition to the above components, for the purpose of improving magnetic properties, appropriately comprises one or two or more selected from in mass% of Ni: 0.001–0.150%, Sb: 0.005–0.500%, Sn: 0.005–0.200%, P: 0.01–0.08%, Bi: 0.005–0.100%, Mo: 0.005–0.100%, B: 0.0002–0.0025%, Cu: 0.01–0.20%, Cr: 0.01–0.20%, Nb: 0.0010–0.0100%, V: 0.001–0.010%, Ti: 0.001–0.010%, and Ta: 0.001–0.010%. You may add it.

[0052] Next, the manufacturing method of the present invention will be described. The manufacturing method may utilize a general method for manufacturing electrical steel sheets. For example, molten steel with a predetermined composition adjustment is formed into a steel slab of the above composition using a conventional ingot casting or continuous casting method. Since it is difficult to add the aforementioned additive components during intermediate processes, it is preferable to add them at the molten steel stage. The steel slab is heated by a conventional method and provided for hot rolling. When the material contains elements that form inhibitors, the heating temperature is preferably 1300°C or higher to ensure solid solution. More preferably, it is 1350°C or higher. Although no upper limit is specifically specified, since the melting point of steel containing Si drops to approximately 1460°C, it is necessary to keep the temperature below that level. For composition systems that do not contain inhibitors, it is preferable to keep the heating temperature at 1250°C or lower from the perspective of cost reduction.

[0053] Next, hot-rolled sheet annealing may be performed as needed. By performing hot-rolled sheet annealing, the microstructure can be homogenized, making it possible to reduce the variation in the magnetic properties of the steel sheet. From the perspective of microstructure homogenization, it is desirable to maintain these annealing conditions at 900°C or higher for at least 15 seconds.

[0054] After the annealing of the hot-rolled sheet above, cold rolling is performed, or after performing intermediate annealing in addition to this cold rolling, cold rolling is performed again to reach the final sheet thickness, and then primary recrystallization annealing is performed. In the above cold rolling, warm rolling is performed by raising the steel sheet temperature to 100 to 300°C, or aging treatment is performed once or multiple times in the range of 100 to 300°C during the cold rolling, which is effective in changing the recrystallization texture and improving magnetic properties.

[0055] In addition, in the above intermediate annealing, it is desirable to maintain the material at 900°C or higher for 30 seconds or more because this is effective for tissue improvement. More preferably, it is maintained at 1000°C or higher for 60 seconds or more.

[0056] In the above first recrystallization annealing, decarburization of the steel sheet may also be performed. From the perspective of decarburization, the annealing temperature of the above first recrystallization annealing is suitable to be 800°C or higher and 900°C or lower. In addition, from the perspective of decarburization, it is desirable to use a humid atmosphere. Furthermore, in the first recrystallization annealing, it is desirable to set the heating rate to the holding temperature in the range of 50°C / s or higher and 1000°C / s or lower to ensure good final magnetic properties.

[0057] Next, in the present invention, it is necessary to apply an annealing separator to the front surface of a steel plate and then perform secondary recrystallization annealing to develop secondary grains having a Goss orientation, and at the same time form an underlayer film composed of ceramic particles such as forsterite. In order to form such forsterite, it is preferable to apply MgO powder suspended in a solution such as water as an annealing separator to a steel plate having silica formed on its surface.

[0058] In the present invention, the presence of S or Se at the grain boundaries of ceramics such as forsterite is required, and if these elements are not included in the material components, it is preferable to mix a material containing S or Se together with MgO. Alternatively, means such as immersion treatment using an H2S atmosphere or a salt bath containing FeS are also considered.

[0059] Here, materials containing S or Se include sulfides, selenides, sulfates, selenates, etc. Secondary recrystallization annealing precisely controls the type of gas introduced as the atmosphere. For example, it is desirable to control the introduction time and introduction start temperature of the H2 atmosphere according to the form of S introduction (whether it is included in the material components or sulfates are introduced during an intermediate process) so that it becomes possible to stably have S or Se present at the ceramic grain boundaries. In particular, controlling the introduction time of the H2 atmosphere is considered important.

[0060] However, the atmosphere control is not the only means for realizing the present invention, and other methods may also be employed. In order to remove (purify) inhibitor components or other impurities from the base metal, it is preferable to maintain the annealing temperature of the secondary recrystallization annealing at 1100°C or higher for 3 hours or more. More preferably, the annealing temperature is 1150°C or higher, and the holding time of the annealing is 5 hours or more. Furthermore, although there are no specific upper limits for these temperatures or holding times, from the perspective of productivity, the upper limit of the temperature is approximately 1275°C, and the upper limit of the holding time is approximately 20 hours.

[0061] After the above secondary recrystallization annealing, it is useful to perform water washing, brushing, or acid washing to remove the attached annealing separator. Afterwards, it is effective to correct the shape by performing additional planarization annealing to reduce iron loss.

[0062] In the present invention, the amount of grain boundary segregation can be measured using a transmission electron microscope or a three-dimensional atom probe (3DAP). When using the transmission electron microscope, the amount of grain boundary segregation can be quantified by performing EDS analysis of the grain boundary under conditions where the sample thickness is 100 nm or less, the acceleration voltage is 40 kV or more, and the beam diameter is 1 nm or less. On the other hand, when using the 3DAP, a needle-shaped sample with a tip adjusted to 200 nm or less is used, and measurement is performed under conditions of a detection efficiency of 20% or more using thermal excitation by laser assist. By extracting the element concentration profile of the region crossing the grain boundary from the obtained three-dimensional ion map, the distribution of elements segregated at the grain boundary and the quantification thereof can be made.

[0063] In addition, regarding the conditions of such manufacturing methods for oriented electrical steel sheets not mentioned above, all may be in accordance with commercial law.

[0064] Examples

[0065] (Example 1)

[0066] A steel slab containing, in mass %, C: 0.062%, Si: 3.30%, Mn: 0.15%, N: 0.0057%, sol. Al: 0.0250%, and Se: 0.013%, with the remainder being Fe and unavoidable impurities, was manufactured by continuous casting, heated to cracking slab at 1400°C for 30 minutes, and finished to a thickness of 2.4 mm by hot rolling. Afterward, hot-rolled sheet annealing was performed at 1050°C for 30 seconds in a dry nitrogen atmosphere. After this hot-rolled sheet annealing, the surface scale was removed by acid cleaning, and the sheet was cold-rolled to a thickness of 1.8 mm. Additionally, intermediate annealing was performed at 950°C for 200 seconds, and the sheet was finished to a thickness of 0.23 mm by cold rolling. Subsequently, primary recrystallization annealing accompanied by decarburization was performed at 830°C for 80 seconds under a humid atmosphere of 50 vol% H2–50 vol% N2 and a dew point of 60°C. Afterward, an annealing separator mainly composed of MgO was applied, and secondary recrystallization annealing was performed at 1200°C for 10 hours. At that time, as described in Table 2, various types of gases were used in each temperature range. In addition, for the heating process up to 800°C not listed in Table 2, the heating process was performed in an N2 atmosphere, and the cooling process was performed in an Ar atmosphere.

[0067] The film adhesion of the samples obtained in this way was evaluated by winding the steel plate onto cylinders of various diameters and determining the minimum diameter at which the film did not peel off. If the minimum diameter of this bending cylinder was 25 mm or less, the film adhesion was judged to be excellent. The results are shown in Table 2.

[0068] In this embodiment, forsterite was formed as an underlayer under all conditions. Using the same method as in Experiment 1, the element enriched at the forsterite grain boundary, the amount present (peak value), and the thickness (peak half-width) in that case were investigated. The results are listed in Table 2. In addition, the investigation was performed at 50 grain boundaries, and the average value was adopted.

[0069]

[0070] From the description in Table 2, it can be seen that a directional electrical steel sheet with excellent film adhesion is obtained under conditions within the scope of the present invention.

[0071] (Example 2)

[0072] A steel slab containing, in mass%, C: 0.025%, Si: 3.12%, Mn: 0.09%, N: 0.0021%, sol. Al: 0.0061%, with the remainder being Fe and unavoidable impurities, was manufactured by continuous casting and subjected to cracking slab heating at 1200°C for 30 minutes, and finished to a thickness of 2.2 mm by hot rolling. Subsequently, hot-rolled plate annealing was performed at 1100°C for 30 seconds in a dry nitrogen atmosphere. After this hot-rolled plate annealing, surface scale was removed by acid cleaning, and the plate was finished to a thickness of 0.23 mm by cold rolling. Subsequently, primary recrystallization annealing accompanied by decarburization was performed at 850°C for 30 seconds under a humid atmosphere of 50 vol% H2–50 vol% N2 and a dew point of 50°C. Afterwards, in addition to MgO, the compound listed in Table 3 was added in the amount listed in Table 3 and coated. Subsequently, a second recrystallization annealing was performed at 1200°C for 5 hours. The atmosphere gas at that time was H2 for 3 hours from the start of the annealing, N2 during the heating process up to 1200°C, and Ar during the latter 2 hours of the annealing and the cooling process.

[0073] The adhesion of the film of the sample obtained in this way was evaluated by winding the steel plate onto a cylinder of various diameters and determining the minimum diameter at which the film did not peel off. The results are shown in Table 3.

[0074] In this embodiment, forsterite was formed as an underlayer under any condition. Using the same method as in Experiment 1, the elements enriched at the forsterite grain boundaries, the amount present (peak value), and the thickness (peak half-width) in that case were investigated. The results are listed in Table 3. In addition, the investigation was performed in the same manner as in Example 1.

[0075]

[0076] From the description in Table 3, it can be seen that a directional electrical steel sheet with excellent film adhesion is obtained under conditions within the scope of the present invention.

Claims

Claim 1 A oriented electrical steel sheet having a base film, wherein the base film comprises ceramic particles, and further, at the grain boundaries of the ceramic particles, one or both of S and Se are present in an amount of 0.02 to 2.00 at%, and the ceramic particles are composed of forsterite. Claim 2 A oriented electrical steel sheet according to claim 1, wherein the S and Se elements are one or more sulfides or selenides selected from Mn, Ca, Sr, Cu, and Mg. Claim 3 A oriented electrical steel sheet according to claim 1 or 2, wherein the thickness between grain boundaries of ceramic particles containing the S and Se elements is 18 nm or more and 50 nm or less. Claim 4 delete

Citation Information

Patent Citations

  • Method for manufacturing oriented electromagnetic steel sheet

    JP2015086437A

  • Method for manufacturing grain-oriented electrical steel sheet

    WO2010047414A1

  • Method for manufacturing grain-oriented electrical steel sheet

    JP2010100885A